Arrangement of the Buluh Cina Natural Tourism Area Teratak Buluh Village Kampar Regency - Puspita Sari, Neri; Yulia, Yulia Setiani; Harnedi, Harnedi Maizir; Ulfa, Ulfa Jusi; Ahmad, Ahmad Hamidi; Desi, Desi Yasri; Haniza, Sjelly Haniza; Silfia, Silfia Rini; Randhy, Randhy Shaily; Ziyar, Zaiyar (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
Taman Wisata Alam (TWA) Buluh Cina is an area that has a beautiful natural atmosphere, surrounded by lush forests, trees, lakes and residential areas. This place is usually crowded with tourists, especially on holidays. TWA Buluh Cina also has a variety of fauna, and what is special are several elephants. Chinese Reed TWA was re-opened with new normal conditions after the Covid 19 outbreak hit. Seeing the current condition of TWA Buluh Tionghoa, it is necessary to make improvements so that the number of visitors returns to be crowded. With a large number of visitors, it can improve the standard of living of the surrounding community, developing UMKM  can indirectly create jobs. The arrangement that was carried out began with field observations. After gathering information on what can be done to organize this area, a plan is drawn up. The activities carried out included installing signboards and cleaning the TWA Buluh cina area. The goal is that the area is more organized, visitors are more comfortable and can more easily travel at the Chinese Bamboo Tour site. This activity involves the academic community of STT Pekanbaru, the government (kelurahan or village) and the local community